Answer:
First system: no solution
Second system: one solution
Third system: one solution
Fourth system: infinite solutions
Fifth system: no solution
Explanation:
First system: 3x-2y=3; 6x-4y=1
From the first equation: y = (3x - 3)/2
Using this value of y in the second equation:
6x - 6x + 6 = 1
6 = 1 -> System has no solution
Second system: 3x-5y=8; 5x-3y=2
From the first equation: x = (8 + 5y)/3
Using this value of x in the second equation:
5*(8 + 5y) - 9y = 6
40 + 25y - 9y = 6
16y = -34 -> y = -2.125
x = (8 - 5*2.125)/3 = -0.875
This system has one solution
Third system: 3x-2y=8; 4x-3y=1
From the first equation: x = (8 + 2y)/3
Using this value of x in the second equation:
4*(8 + 2y) - 9y = 3
32 + 8y - 9y = 6
y = 26
x = (8 + 2*26)/3 = 20
This system has one solution
Fourth system: 3x-6y=3; 2x-4y=2
From the first equation: x = 1 + 2y
Using this value of x in the second equation:
2*(1 + 2y) - 4y = 2
2 + 4y - 4y = 2
2 = 2
This system has infinite solutions
Fifth system: 3x-4y=2; 6x-8y=1
From the first equation: x = (2 + 4y)/3
Using this value of x in the second equation:
2*(2 + 4y) - 8y = 1
4 + 8y - 8y = 2
4 = 2
This system has no solution